2020
DOI: 10.1002/hon.2715
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity assessment to determine prognosis in older adult patients with classical Hodgkin lymphoma

Abstract: The clinical management of older adult patients with Hodgkin lymphoma (HL) remains a major challenge. The aim of this study was to evaluate the impact of comorbidity assessment according to a standardized approach, the Cumulative Illness Rating Scale (CIRS), on prognosis in patients with classical HL aged 60 years and older. We studied 76 consecutive older adult patients with HL (median age 69 y, range 60‐84) who had been treated in our institution between 1999 and 2018. Comorbidity was assessed at diagnosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The major trials included small numbers of elderly patients and there have been few prospective trials for older patients. Frailty, as assessed by formal scores such as the cumulative illness rating score (CIRS) is a strong predictor of OS in elderly HL 61 and the UK Shield registration study 62 has shown that frail patients are consistently unable to complete treatment.…”
Section: Management Of Hodgkin Lymphoma In Elderly Patientsmentioning
confidence: 99%
“…The major trials included small numbers of elderly patients and there have been few prospective trials for older patients. Frailty, as assessed by formal scores such as the cumulative illness rating score (CIRS) is a strong predictor of OS in elderly HL 61 and the UK Shield registration study 62 has shown that frail patients are consistently unable to complete treatment.…”
Section: Management Of Hodgkin Lymphoma In Elderly Patientsmentioning
confidence: 99%
“…Unlike in our study, patients aged ≥60 years were included in the study of Galli et al 24 While 54% of the cases in that study had CIRS ≥3, among our cohort, 30.6% of the patients ≥60 years had CIRS >3. In patients aged ≥60 years and receiving upfront ABVD, CR rate in our cohort was higher than that observed in that study (81% vs 92.7%).…”
Section: Discussionmentioning
confidence: 78%
“…Comorbid conditions chiefly comprise cardiovascular disease, hypertension, chronic obstructive pulmonary disease, and diabetes. In multivariate analyses of elderly HL patients, comorbidity, but not age (60 or older), was regarded as a significant factor of overall survival, whereas the presence of a comorbidity, stage, and presence of B symptoms were each independently correlated with inferior survival [ 24 ]. The presence of comorbidity as an independent prognostic factor is particularly relevant for older patients.…”
Section: Discussionmentioning
confidence: 99%